Ultrasound Application for Oil Extraction of Lemongrass Parts - Yuniarto, Kurniawan, Mr; Welt, Bruce Ari, Prof; Muvianto, Cahyo Mustiko Okta, Dr; Muiz, Abdul, Mr (Makara Journal of Technology, 2022)
Power ultrasound creates acoustic cavitation bubbles that encourage shears within food substances. Applying ultrasound improves solvent diffusion into the matrix plant cellular and hence breaks down bioactive substances. This research aims to extract lemongrass oil using ultrasound-assisted extraction (UAE). The essential oil was extracted from different lemongrass parts, such as corm, stalk, and leaf. Then, a 37 kHz UAE was applied below the solvent vapor pressure temperature under different periods, i.e., 15, 30, and 60 min. The solvent temperature logarithmically increased from 28 ℃ to 53 ℃ during 20 min of the ultrasound treatment. Acoustic power was obtained from a graphic plot by approximately 35.68 kJ for the initial 20 min and by 31.14 kJ for the remaining UAE period. The lemongrass oil obtained a higher yield from the corm section about 3 and 1.4 times compared to stalk and leaf components. The extracted lemongrass oil produced a yellowish color from the leaf and stalk and a yellow-red color from the corm. The refractive index varied between 1.389 and 1.422, and the specific gravity was from 0.89 to 0.97 g/cm3 . The lemongrass leaf produced the highest citral content and more saturated lipid acids than unsaturated in the lemongrass essential oil.